Barrett's esophagus. Practical issues for daily routine diagnosis - Vieth, Michael; Langner, Cord; Neumann, Helmut; Takubo, Kaiyo (Pathology Research and Practice, 2012)
Most clinicians and researchers agree that Barrett's esophagus (BE) is a precancerous condition which, however, is not easily defined. Whether goblet cells must be present or not is a matter of debate and definitions vary worldwide. Although the use of the term " columnar metaplasia" tends to circumvent these issues, it can also be subdivided into those with and without goblet cells. There is some evidence that Barrett's esophagus results from a multistep process in which goblet cells are a secondary event. Hence, Barrett's adenocarcinoma has recently been shown to originate from areas lacking goblet cells. The histological diagnosis of neoplasia is often hampered by marked interobserver variation. New endoscopic techniques allow for local resections of neoplasia with curative intent. Pathologists should know which pieces of information gastroenterologists need for management options: surveillance versus therapy such as endoscopic resection with or endoscopic ablation without histological specimen. The most important information for gastroenterologists is whether there is neoplasia or not; if any, they need to know the grade (low grade, high grade, carcinoma) and risk factors (vessel permeation, poor differentiation, resection complete in case of endoscopic resection, depth of infiltration). © 2012 Elsevier GmbH.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Barrett; Dysplasia; Esophagus; Metaplasia; Neoplasia